MODEL ZA POVEĆANJE IZDRŽLJIVOSTI KANDIDATKINJA ZA PRIJEMNI ISPIT FAKULTETA SPORTA I FIZIČKOG VASPITANJA - Milan Šolaja; Ilona Mihajlović; Miroslav Smajić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In order to increase aerobic capacity and the level of endurance while running it is neccessary to apply efficient methods for increasing abilities already mentioned. One of the ways which gradually introduces those who exercise into the practise is to set the tempo of running at a level 20% higher than the current abilities for the whole lenght of a distance , and the lenght of the running sections should be about 20 % of the entire lenght of the distance. Total amount of the running sections should be 20 % longer than the lenght of the entire distance. The lenght of each section should be gradually increased , and breakes should be gradually decreased. The speed of running is obtained and those who exercise are adapted to the tempo of running , which results in rapid development of the adaptation to increased efforts. This makes possible to achieve statisticly significant increasement of endurance in running 800 meters in a short period of time , in just four weeks , with three trainings per week. The advantage of this model is that it could be used for rapid increasement of running endurance in number of sport disciplines.